Transcriptomic and Proteomic Analyses Reveal the Potential Mode of Action of Chondrocyte Sheets in Hyaline Cartilage Regeneration - Toyoda, Eriko (Int J Mol Sci, 2019)
Chondrocyte sheet transplantation is a novel and promising approach to treating patients who have cartilage defects associated with osteoarthritis. Hyaline cartilage regeneration by autologous chondrocyte sheets has already been demonstrated in clinical research. In this study, the efficacy of polydactyly-derived chondrocyte sheets (PD sheets) as an allogeneic alternative to standard chondrocyte sheets was examined using an orthotopic xenogeneic transplantation model. In addition, the expression of genes and the secreted proteins in the PD sheets was analyzed using a microarray and a DNA aptamer array. The efficacy of PD sheets with respect to cartilage defects was assessed using histological scores, after which the expressions of genes and proteins exhibiting a correlation to efficacy were identified. Enrichment analysis of efficacy-correlated genes and proteins showed that they were associated with extracellular matrices, skeletal development, and angiogenesis. Eight genes (ESM1, GREM1, SERPINA3, DKK1, MIA, NTN4, FABP3, and PDGFA) exhibited a positive correlation with the efficacy of PD sheets, and three genes (RARRES2, APOE, and PGF) showed a negative correlation for both transcriptomic and proteomic analyses. Among these, MIA, DKK1, and GREM1 involved in skeletal development pathways and ESM1 involved in the angiogenesis pathway exhibited a correlation between the amount of secretion and efficacy. These results suggest that these secreted factors may prove useful for predicting PD sheet efficacy and may therefore contribute to hyaline cartilage regeneration via PD sheets.